STRUCTURES AND STRUCTURAL INTERSECTION: THEORY AND PRACTICE - Jonavičius, Laurynas (Politologija, 2015)
Theoretical concepts of “structure” and “structural intersection” are analysed in this article. The use of these concepts in political science and their critical interpretation is presented by analyzing positivist, ideational and post-modernist approaches. Sociological understanding of structure, which encompasses both material and ideational elements is created. Under the suggested definition, structure is seen as comprised of identity, institutions and material base. The interaction of these structural elements forms scientifically usefull concept, which can be applied in the analysis of the socio-political processes in post-soviet transformations. Opportunities and limitations of “structural intersection” analysis, which include both international relations and internal policy perspectives are also presented. Though term “structural intersection” is often used in Lithuanian academic discourse, its understanding is still very vague. This paper’s goal is to present short overview how the term “structure” has been used in political science. Based on the analysis of different theories in political sciences, international relations and sociology, integrated concept of structure is created. The definition of structure includes three main elements: identity, institutions and material base, each of them forming separate structural dimension, which interact and have integrated constitutive effect on agents’ behaviour. Presented theoretical approach is based on ideational ontology and sees the reality as a complex set of interactions between ideas, mental-cognitive models and material elements. It is maintained that the elements of structural realism, constructivism and new institutionalism theories should be alltogether incorporated into the socio-political reaserach. Though it makes any social reasearch very complex, it provides the investigator with an opportunity to understand the context and circumstances (both ideational and material) in which the subject of analysis is embeded. Since political world is comprised of the subjects that have different undersating of their role, goals and place in the world, “structural understanding” is necessary in order to choose appropriate tools and resources in the research process. Practical recomendations, which are inseperable element of all social science also can be better appraised with the use of “structural understanding”. Empirical application of the “structural reasearch model” is presented using the cases of Russian and European structures and the impact of their intersection on post-soviet trarnsformational processes.